1993
DOI: 10.1212/wnl.43.5.962
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory testing differentiates between progressive supranuclear palsy and idiopathic Parkinson's disease

Abstract: Olfactory dysfunction occurs in most patients with idiopathic Parkinson's disease (PD). In this study, we sought to determine whether such dysfunction is also present in progressive supranuclear palsy (PSP), a condition which shares a number of motor symptoms with PD and is commonly misdiagnosed as PD. We administered the University of Pennsylvania Smell Identification Test, a standardized test of odor identification ability, to 21 PSP patients; 17 also received a forced-choice odor detection threshold test. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
84
3
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(95 citation statements)
references
References 4 publications
5
84
3
2
Order By: Relevance
“…The deficit in olfaction in PD contrasts with previous reports of preserved or only mildly reduced olfaction in patients with atypical parkinsonism such as a tauopathy or multiple system atrophy (MSA) (Doty et al, 1993;Wenning et al, 1995). In dementia patients, neuropathologic studies reported neuronal alterations in several subcortical structures such as the olfactory tract/bulb, anterior olfactory nucleus, orbito-frontal cortex, hippocampus, and amygdala in the olfactory system (Hubbard et al, 2007).…”
Section: Olfactory Dysfunctioncontrasting
confidence: 71%
“…The deficit in olfaction in PD contrasts with previous reports of preserved or only mildly reduced olfaction in patients with atypical parkinsonism such as a tauopathy or multiple system atrophy (MSA) (Doty et al, 1993;Wenning et al, 1995). In dementia patients, neuropathologic studies reported neuronal alterations in several subcortical structures such as the olfactory tract/bulb, anterior olfactory nucleus, orbito-frontal cortex, hippocampus, and amygdala in the olfactory system (Hubbard et al, 2007).…”
Section: Olfactory Dysfunctioncontrasting
confidence: 71%
“…[11][12][13] Loss of neurons and Lewy body deposition are also noted in the anterior olfactory bulb in PD.…”
mentioning
confidence: 99%
“…This can make accurate diagnosis challenging, especially in the early stages of disease 8. Since PSP is not known for specific olfactory pathology, this suggests that the UPSIT test might be used for differential diagnosis of PD versus PSP, as demonstrated previously 16. We offer preliminary support for the possibility that the specific pattern of responses on the test can be used in a similar way to distinguish PD from PSP (AUC = 0.91); however, sample size for this particular comparison is limited in our dataset and so this result should be considered speculative.…”
Section: Resultsmentioning
confidence: 97%